The Liver-Stage Plasmodium Infection Is a Critical Checkpoint for Development of Experimental Cerebral Malaria - Sato, Yuko; Ries, Stefanie; Stenzel, Werner; Fillatreau, Simon; Matuschewski, Kai (Frontiers in Immunology, 2019)
Cerebral malaria is a life-threatening complication of malaria in humans, and the underlying pathogenic mechanisms are widely analyzed in a murine model of experimental cerebral malaria (ECM). Here, we show abrogation of ECM by hemocoel sporozoite-induced infection of a transgenic Plasmodium berghei line that overexpresses profilin, whereas these parasites remain fully virulent in transfusion-mediated blood infection. We, thus, demonstrate the importance of the clinically silent liver-stage infection for modulating the onset of ECM. Even though both parasites triggered comparable splenic immune cell expansion and accumulation of antigen-experienced CD8+ T cells in the brain, infection with transgenic sporozoites did not lead to cerebral vascular damages and suppressed the recruitment of overall lymphocyte populations. Strikingly, infection with the transgenic strain led to maintenance of CD115+Ly6C+ monocytes, which disappear in infected animals prone to ECM. An early induction of IL-10, IL-12p70, IL-6, and TNF at the time when parasites emerge from the liver might lead to a diminished induction of hepatic immunity. Collectively, our study reveals the essential role of early host interactions in the liver that may dampen the subsequent pro-inflammatory immune responses and influence the occurrence of ECM, highlighting a novel checkpoint in this fatal pathology.